The Mediating Effects of Environmental Disclosures on the Effect of Environmental Performance on Profitability (Survey of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2013-2015) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the mediating effect of environmental disclosure on the effect of environmental performance on profitability. This study uses reports of companies engaged in the manufacturing sector, with the criteria of the report disclosing social and environmental information in the annual report (annual report) during the 2013-2015 period and revealing the results of an assessment of the company performance rating assessment program in environmental management (PROPER) during the period 2013-2015. The research method used in this research is explanatory research or explanatory research. This study shows that the relationship between variables is causal, so it is included in the type of causal research. The analytical methods used in this study are descriptive statistics, classic assumption tests, hypothesis testing and path analysis. Hypothesis testing results show that environmental performance has a positive effect on profitability (ROA) and environmental disclosure while environmental disclosure has no effect on profitability. Hypothesis testing results show that environmental performance has an influence on environmental disclosure then to profitability. The path analysis results show that in this study environmental disclosure is not able to mediate the effect of environmental performance on profitability.